Sonderangebote und Preissynchronisation im deutschen Lebensmitteleinzelhandel; Sales and Price Synchronization in German Food Retailing - Angela Hoffmann; Jens-Peter Loy (German Journal of Agricultural Economics (GJAE), 2010)
– German food retailing is characterized by a strong price competition. Thus, we would expect the law of one price to hold and price adjustments to occur simultaneously. However, significant price differences can be observed which are often caused by sales. As price promotions are not related to supply or demand changes, they might bias measures of price synchronization. As dairy products are a key category that is often used in sales, we study the impact of price promotions on measures of price synchronization using dairy product prices in the German food retail market. Our results show with a very few exceptions that price promotions significantly bias the measures of price synchronization within and between stores. Over all stores and products 25% of regular prices are synchronized but only 10% of promotional prices occur simultaneously. Discounters synchronize regular price changes to a greater extent and promotional prices to a lesser extent. The level of price synchronization between stores indicates a positive correlation with the number of competitors and with the level of menu costs. Price synchronization is lower for perishable compared to durable products. Also, some store and chain effects are observed. Within stores, regular price changes of substituting brands are highly synchronized whereas price promotions are staggered within the same category.
Keywords: 330; Lebensmitteleinzelhandel; Sonderangebot; Preiswettbewerb; Deutschland